The Relevance ff Law Number 12 Of 2022 on Efforts To Protect The Rights ff Women Victims ff Sexual Harassment Feminist Legal Theory Perspective - Faqih Fiddin, Abdullah; Kusumawati, Ita Rahmania (Mauriduna: Journal of Islamic Studies, 2024)
Kejadian pelecehan seksual termasuk cat calling merupakan suatu bentuk kekerasan pada Perempuan yang menjadi sebuah permasalahan khusus yang sering terjadi disekitar kita. Terlebih yang terjadi dilingkungan kampus yang korbannya tentunya para mahasiswi yang berada dikampus tersebut. Tujuan penelitian ini adalah menganalisis relevansi Undang – Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual dalam upaya perlindungan hak Perempuan korban pelecehan seksual, khususnya cat calling dengan menggunakan perspektif feminist legal theory. Penelitian ini menggunakan pendekatan kualitatif dengan sumber data utama berupa wawancara dengan mahasiswi kampus Unhasy yang mengalami cat calling. Selain itu data juga diperoleh melalui observasi dan studi dokumentasi. Analisis data dilakukan dengan metode deskriptif dan interpretasi. Merujuk pada hasil penelitian menunjukan bahwa UU Nomor 12 Tahun 2022 memiliki relevansi dalam upaya perlindungan hak Perempuan korban pelecehan seksual termasuk cat calling. Namun perspektif feminist legal theory mengkritisi adanya bias patriarki yang dapat menghambat keadilan serta kesetaraan gender dalam perlindungan hukum. Hal inilah yang menjadi sorotan tentang pentingnya pemberdayaan Perempuan dan penghapusan diskriminasi dalam upaya mencapai keadilan dan perlindungan hak Perempuan. Incidents of sexual harassment, including catcalling, are a form of violence against women which is a special problem that often occurs around us. Moreover, what happened on campus was that the victims were of course female students on campus. This research aims to analyze the relevance of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence in efforts to protect the rights of women who are victims of sexual harassment, especially catcalling, using a feminist legal theory perspective. This research uses a qualitative approach with the main data source being interviews with Unhasy campus students who experienced catcalling. Apart from that, data was also obtained through observation and documentation studies. Data analysis was carried out using descriptive and interpretation methods. Referring to the research results, show that Law Number 12 of 2022 has relevance in efforts to protect the rights of women who are victims of sexual harassment, including catcalling. However, the feminist legal theory perspective criticizes the existence of patriarchal bias which can hinder justice and gender equality in legal protection. This highlights the importance of empowering women and eliminating discrimination in efforts to achieve justice and protect women's rights.